2001
DOI: 10.1017/s0048577201991140
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactions in children: Verbal, physiological, and behavioral responses to affective pictures

Abstract: Many studies have shown a consistent pattern in adults' responses to affective pictures and there is growing evidence of gender differences, as well. Little is known, though, about children's verbal, behavioral, and physiological responses to affective pictures. Two experiments investigated children's responses to pictures. In Experiment 1, children, adolescents, and adults viewed pictures varying in affective content and rated them for pleasure, arousal, and dominance. Results indicated that children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
103
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 0 publications
16
103
1
4
Order By: Relevance
“…Second, we obtained ratings from both children and adolescents, thereby extending the developmental period for which emotional data are available. In line with McManis et al (2001), our study confirms that, from the age of 7 years on, children are able to use the pictorial 9-point SAM scale to rate words on the valence and arousal dimensions. Despite the significant correlations between the four age groups' ratings (i.e., age 7, age 9, age 11, and age 13), we also found age-related differences.…”
Section: Resultssupporting
confidence: 88%
“…Second, we obtained ratings from both children and adolescents, thereby extending the developmental period for which emotional data are available. In line with McManis et al (2001), our study confirms that, from the age of 7 years on, children are able to use the pictorial 9-point SAM scale to rate words on the valence and arousal dimensions. Despite the significant correlations between the four age groups' ratings (i.e., age 7, age 9, age 11, and age 13), we also found age-related differences.…”
Section: Resultssupporting
confidence: 88%
“…There are also differences between studies in gender ratio, distribution of subtypes and the presence of comorbid disruptive behavior disorders. Gender ratio may affect the results because previous studies found girls to be more reactive to unpleasant pictures and to experience more difficulties in regulating negative emotions than boys (Bender, ReinholdtDunne, Esbjørn, & Pons, 2012;McManis et al, 2001;Neumann, van Lier, Gratz, & Koot, 2010;Suveg & Zeman, 2004). It should however be noted that in the current study both groups had an equal gender ratio, and the fact that earlier studies that included exclusively boys did also find emotion regulation deficits in ADHD, goes against this view (Köchel et al, 2014;López-Martín et al, 2013).…”
Section: Discussioncontrasting
confidence: 64%
“…The children were instructed to evaluate the picture and to approach or avoid it by pressing one of two marked keys on the computer keyboard. The pictures were a selection of 30 positive (e.g., chocolate, smiling children) and 30 negative pictures (e.g., a snake, a wounded person) from the International Affective Picture System (IAPS; Center for the Study of Emotion and Attention [CSEA-NIMH], 1999;Lang, Bradley, & Cuthbert, 2008), chosen to be suitable for children (McManis, Bradley, Berg, Cuthbert, & Lang, 2001). There were two conditions, a congruent and an incongruent condition, presented in a random order.…”
Section: Methodsmentioning
confidence: 99%